THE IMPACT OF SOCIAL ENTREPRENEURSHIP ON THE ECONOMIC ACTIVITY OF VULNERABLE POPULATION GROUPS - DRUHOVA, Olena; LYPOVYI, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article explores the impact of social entrepreneurship on the economic activity of vulnerable population groups. Social entrepreneurship is an innovative activity that combines economic efficiency with achieving social goals. The study emphasizes the importance of social enterprises in addressing critical societal issues by creating jobs, providing professional training, and promoting social integration for marginalized groups, including persons with disabilities, internally displaced persons, single mothers, and the unemployed. The article analyzes international practices in developing social enterprises, highlighting the experiences of the United Kingdom, Germany, France, Canada, and South Korea, and identifies opportunities for adapting these best practices to the Ukrainian context. Special attention is paid to the role of social enterprises in fostering inclusive environments and overcoming barriers related to stereotypes and discrimination. The dual mission of social enterprises – ensuring financial sustainability and addressing societal challenges – is underlined as their distinctive feature compared to traditional business models. Key challenges facing social entrepreneurship in Ukraine are identified, including inadequate legislative frameworks, limited financial resources, and a lack of public awareness about the benefits of this sector. The study highlights the need for comprehensive measures to support social enterprises at the national level, including legislative improvements, tax incentives, and state-funded grants. The importance of introducing educational programs to develop skills and raise awareness about social entrepreneurship among entrepreneurs and the general population is also emphasized. Furthermore, the study emphasizes the importance of investment in social enterprises. Over the period analyzed, significant growth in employment within social enterprises, increased investment levels, and a rise in the number of active social enterprises were observed despite the challenging economic environment in Ukraine. These trends indicate the sector’s resilience and potential for sustainable development.